WORKPLACE INTIMIDATION AND ORGANIZATIONAL COMMITMENT IN DEPOSIT MONEY BANKS IN RIVERS STATE, NIGERIA (American Journal of Research in Humanities and Social Sciences, 2023)
This study investigated the impact of workplace intimidation on organizational commitment among 200 randomly selected employees from ten deposit money banks in Rivers State, Nigeria. Using a cross-sectional survey design and questionnaire method, data was collected and analyzed using the Kendall Tau_b statistical technique. Results indicated a negative correlation between intimidation as an impression management strategy and organizational commitment dimensions (affective, normative, and continuance). It was concluded that such intimidation significantly undermines employees' commitment to the organization. The study recommends discouraging practices like verbal abuse, threats, sexual harassment, and other negative behaviors to promote commitment. Additionally, it suggests severe consequences for offenders to deter such behavior and presents theoretical, managerial, and practical implications for reducing intimidation and enhancing organizational commitment in deposit money banks.